A New Slip Length Model for Enhanced Water Flow Coupling Molecular Interaction, Pore Dimension, Wall Roughness, and Temperature - Lei Li; Yuliang Su; Han Wang; Guanglong Sheng; Wendong Wang (Advances in Polymer Technology)
In this paper, a slip length model is proposed to analyze the enhanced flow based on the Hagen–Poiseuille equation. The model considers the multimechanisms including wall-water molecular interactions, pore dimensions, fractal roughness, and temperature. The increasing wall-water interactions result in the greater slip length and flow enhancement factor. The increased temperature enhances the kinetic energy of water molecules that leads to great surface diffusion coefficient and small work of adhesion. The wall roughness can decrease the slip length and flow enhancement factor in hydrophilic nanopores. This work studies the effects of multimechanisms on slip length and flow enhancement factor theoretically, which can accurately describe the liquid flow in nanopores.